Analysis Of Business Feasibility Of Bio Solid Rubber (Bsr) As A Content Of Rubber Vibration - Anissa Anissa; Adelia Anggraini; Sri Maulana Putri; Yudha Andriansyah Putra (JASc (Journal of Agribusiness Sciences), 2019)
Rubber plants have a big role in Indonesia's economic life. Many people live by relying on rubber plantations as their business commodities and especially for those living in the countryside. The fruit of the Mengkudu is one of the plants that is rich in benefits. In addition to the medical world, the Mengkudu juice can also be utilized as one of the alternative ingredients for the use of latex acid replacement formiat. Acid content in the fruit of the mengkudu when mixed with latex, it will form coagulants. The coagulant is used in the form of a mengkudu fruit. The juice of the mengkudu that is used is the fruit juice of ripe mengkudu and juice Mengkudu peram. Coagulation using a yam cider starch is a natural-based coagulation that is safe for farmers despite the cyanide content (HCN) Business feasibility study is required to see a description of the feasibility or unworthiness of the business that will Done. The research aims to see if the BSR business as a rubber cilier is feasible or not to do. Every aspect that is said to be worthy should have a certain standard of value, but judgment is not only done in one aspect. The assessment for determining eligibility should be based on several aspects. The method used in this research is the method of SWOT analysis (strength, weaknesses, opportunities, threats), economic analysis of the business which includes: (Calculating the price of production, selling price, profit, and Ratio) and also using the way Marketing strategies that include: (Product strategy, pricing strategy, place strategy and also promotion strategy). From the results of the study showed that BSR business is worthy to run and has excellent prospects.